1983
DOI: 10.1073/pnas.80.10.2951
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human fibroblast growth rate by both noncycling cell fraction transition probability is shown by growth in 5-bromodeoxyuridine followed by Hoechst 33258 flow cytometry.

Abstract: Growth of human diploid fibroblasts in the presence of 5-bromodeoxyuridine, followed by flow cytometric analysis of DNA-specific fluorescence with Hoechst 33258 dye, allows quantitation of the proportion of cells that have not cycled, as well as those in G1 and G2 of two subsequent cell cycles. This technique allows rapid and accurate quantitation of the growth fraction and G1/S transition rate of these cells. The cell cycle kinetics of human diploid fibroblasts at all population doubling levels reveal two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 32 publications
7
67
0
Order By: Relevance
“…16,17 This technique allows a retrograde assessment of cell cycle history: quiescent G 0 /G 1 -cells (normal PI and normal Hoechst fluorescence) can be distinguished from cells in G 1 -phase, which have completed a cell cycle (normal PI but reduced Hoechst fluorescence). Interestingly, E2F1 and E2F2 but not E2F4 were able to induce mitosis of cardiomyocytes although all of them induced S-phase.…”
Section: Behind the Restriction Point: Induction Of G 2 /M-transitionmentioning
confidence: 99%
“…16,17 This technique allows a retrograde assessment of cell cycle history: quiescent G 0 /G 1 -cells (normal PI and normal Hoechst fluorescence) can be distinguished from cells in G 1 -phase, which have completed a cell cycle (normal PI but reduced Hoechst fluorescence). Interestingly, E2F1 and E2F2 but not E2F4 were able to induce mitosis of cardiomyocytes although all of them induced S-phase.…”
Section: Behind the Restriction Point: Induction Of G 2 /M-transitionmentioning
confidence: 99%
“…It remained possible that cardiomyocytes arrested either in G1- 16 or in G2-phase and thereby mimicked a hypertrophic phenotype as described earlier for E2F1. 17 We therefore used the flowcytometric BrdU-Hoechst assay, which allows retrospective assessment of G1, S, and G2/M cell cycle phases of synchronous and asynchronous cell populations 11,12 (Figure 4). In the absence of BrdU, all cells within G1-phase (either growth arrested or after mitosis) showed the same intensity of fluorescence for PI and Hoechst 33258 ( Figure 4B).…”
Section: Expression Of E2f1 and E2f2 But Not Of E2f4 Induces Mitosimentioning
confidence: 99%
“…11 The cell cycle profile was calculated using MultiCycle software (Phoenix Flow Systems). Proliferation of cardiomyocytes was determined using the BrdU-Hoechst method, 11 which allows enumeration of cells at different stages of three consecutive cell cycles including mitotic cell division. 12 All FACS analyses were restricted to MF20-positive cells to exclude contaminating fibroblasts.…”
Section: Adenoviruses Cell Culture and Facsmentioning
confidence: 99%
“…Smith and Martin model considered here has sound experimental confirmation (Robinson et al, 1976;Shields, 1978;Shields et al, 1978;Ronning and Seglen, 1982;Rabinovich, 1983) and served as a basis for theoretical models describing the curves of labeled mitoses (Cain and Chau, 1997). We have demonstrated that the model of Smith and Martin is less accurate in describing our experimental data than is our model ascribing the major role in the heterogeneity of proliferation rates to the dispersion of the rates of cell-cycle progression in a deterministic phase.…”
Section: Discussionmentioning
confidence: 58%